National Self-Determination - Heater, Derek. author. aut Link
XIII, 225 p.
Keywords: This study critically examines Woodrow Wilson's acceptance of the principle of national self-determination and his role in implementing it at the Paris Peace Conference of 1919. The assessment includes judgements by his contemporaries and historians of Wilson and the peace settlement. A survey of the manner in which national self-determination shaped the settlement leads to a discussion of the subsequent effects of the idea on the states and territories subject to the Versailles Treaty and related treaties.